2016
DOI: 10.1111/ped.12859
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of small for gestational age (SGA) and short stature in children born SGA who qualify for growth hormone treatment at 3 years of age: Population‐based study

Abstract: The prevalence of SGA and short stature in children born SGA who qualify for GH treatment is approximately 1 of 30 infants and 1 of 1800 children, respectively. The risk is increased when children are born <34 weeks GA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 12 publications
0
32
0
Order By: Relevance
“…However, the majority of the above-mentioned reports do not completely list birth weight, height, or gestational age, making it difficult to confirm whether the patients were truly SGA or not. Taking into consideration that the incidence of SGA in the general population is 2.3–10% ( 11 , 12 , 13 ), we suspect that SGA is a characteristic feature of ACRDYS. Accumulating more precise data should clarify whether the prevalence of SGA is increased in ACRDYS.…”
Section: Discussionmentioning
confidence: 96%
“…However, the majority of the above-mentioned reports do not completely list birth weight, height, or gestational age, making it difficult to confirm whether the patients were truly SGA or not. Taking into consideration that the incidence of SGA in the general population is 2.3–10% ( 11 , 12 , 13 ), we suspect that SGA is a characteristic feature of ACRDYS. Accumulating more precise data should clarify whether the prevalence of SGA is increased in ACRDYS.…”
Section: Discussionmentioning
confidence: 96%
“…A Japanese study on children born between 2006 and 2008 found the SGA prevalence to be 3.5%. [6] The increasing prevalence of term newborns less than 2400gr was noticed in Korea, from 3.0% in 1995 to 4.6% in 2007. [7] A Swedish study reported 5.4% SGA, [8] while the highest observed prevalence was observed in South Asia and in Saharan countries of Africa.…”
Section: Growth Hormone Treatment In Children Born Small For Gestatiomentioning
confidence: 99%
“…Fujita et al reported that the incidence of severe SGA (birthweight less than À2 standard deviations (SD) for gestational age) was 1.2% in their population-based study conducted in Kobe. 2 Fujioka et al reported that infants with severe SGA have abnormal placental DNA methylation, which suggested of disturbed epigenetic control in utero. 3 These findings suggest that severe SGA is more frequently complicated by hypospadias.…”
Section: Introductionmentioning
confidence: 99%